Modelling complexities of learner’s in handling web texts via abstract scene analysis / Nasiroh Omar - Omar, Nasiroh (Penerbit UiTM, 2014)
Handling Web texts is a must activity for learners in higher education. Learners constantly seek, read and retrieve text from the Web. Yet, there is lack of existing system that provides an integrated environment for learners to self-assess their capability of handling the Web text and receive instant feedback in a real-life setting. This paper presents a grounding work on understanding complexities in Web text-handling activities at temporal level to gain its temporal contexts and interaction semantics. This work employs goal directed approach to orchestrate four personas in their respected scenarios. Then, the personas and scenarios are carefully examined by using abstract scene analysis in order to produce two models of Web text-handling activities. These models have been used as the bases for the Web Text-handling Support System implemented as part of the research.